(untitled) (Teaching and Learning Inquiry, 2025)
Trust is fundamental for effective student engagement with feedback in higher education. This study aimed to develop a conceptual framework delineating the specific instructor practices and learning environment conditions that facilitate trustful feedback processes. Open-ended survey responses from higher education instructors (n=147) were analysed using a qualitative methodology. Analysis revealed three key environmental conditions for building trust-based relationships: positive non-judgment; inclusion, community, and constructive interdependence; and dialogue and discussion. Three instructor feedback practices were found to promote student agency: showing empathy and sensitivity to student identities, communicating high expectations, and promoting student self-evaluation. These relationship- building conditions and agency-promoting practices operate synergistically, as represented by our framework of Building Trust Through Feedback. By continuously cultivating this interplay of environmental and relational factors, instructors can engender greater reciprocity, vulnerability, and growth during the feedback process. The proposed framework provides guidance on trust-building pedagogies that enhance student engagement and learning. Further research should explore student perspectives on practices that build trusting instructor-student relationships.